2020
DOI: 10.1016/j.jstrokecerebrovasdis.2020.105212
|View full text |Cite
|
Sign up to set email alerts
|

Posterior Reversible Encephalopathy Syndrome in Patients with Coronavirus Disease 2019: Two Cases and A Review of The Literature

Abstract: Highlights Posterior reversible encephalopathy syndrome may be associated with coronavirus disease. Risk factors may include modest blood pressure fluctuations and anakinra. All reported patients had clinical improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
57
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(59 citation statements)
references
References 31 publications
0
57
0
2
Order By: Relevance
“…Although the CSF RBC count was only reported for 61/430 (14%) patients [ 22 , 28 , 29 , 31 , 35 , 39 , 40 , 44 , 73 , 74 , 77 , 78 , 81 , 89 , 92 , 102 , 110 , 118 , [120] , [121] , [122] , [123] , 128 , 133 , 134 , [138] , [139] , [140] , 156 , 165 , 166 , [172] , [173] , [174] , [175] , [176] , 180 , 184 , 188 , 191 , 192 , 198 , 202 , 204 , 208 , 215 , 220 , 225 , 227 , 233 , 241 , 242 , 246 ], the CSF white blood cell (WBC) count was provided for 409/430 (95%) patients, 270 (66%) of whom had >0 cells/μL, >1 WBC:1,000 RBC or were noted to have “pleocytosis” ( Fig. 3 ) [ [5] , [6] , [7] , [8] , 10 , 13 , [15] , [16] , [17] , [18] ...…”
Section: Resultsmentioning
confidence: 99%
“…Although the CSF RBC count was only reported for 61/430 (14%) patients [ 22 , 28 , 29 , 31 , 35 , 39 , 40 , 44 , 73 , 74 , 77 , 78 , 81 , 89 , 92 , 102 , 110 , 118 , [120] , [121] , [122] , [123] , 128 , 133 , 134 , [138] , [139] , [140] , 156 , 165 , 166 , [172] , [173] , [174] , [175] , [176] , 180 , 184 , 188 , 191 , 192 , 198 , 202 , 204 , 208 , 215 , 220 , 225 , 227 , 233 , 241 , 242 , 246 ], the CSF white blood cell (WBC) count was provided for 409/430 (95%) patients, 270 (66%) of whom had >0 cells/μL, >1 WBC:1,000 RBC or were noted to have “pleocytosis” ( Fig. 3 ) [ [5] , [6] , [7] , [8] , 10 , 13 , [15] , [16] , [17] , [18] ...…”
Section: Resultsmentioning
confidence: 99%
“…According to the Literature, the majority of PRES patients had severe respiratory manifestations of COVID-19 requiring intensive respiratory support. PRES can develop also in asymptomatic COVID-19 patients [ 33 ]. The high number of COVID-19-related PRES cases can be also due to large use of interleukin 1 and 6 inhibitors (Anakinra and Tocilizumab) in COVID-19 therapy: these drugs can directly act on endothelial function favouriting typical PRES alterations [ 20 , 34 37 ].…”
Section: Posterior Reversible Encephalopathy Syndrome (Pres) In Covidmentioning
confidence: 99%
“…In 60% of patients with clinically suspected PRES brain MRI was normal. In about 40% of cases, typical PRES pattern is seen with often mild, posterior, bilateral, quite symmetric oedema [ 33 ]. In COVID-19 setting, as seen in our cases, there is an increased rate (10–30% of patients) of deep white matter, basal ganglia and cerebellum involvement as well as haemorrhagic contamination [ 14 , 38 , 39 ], cytotoxic oedema (diffusion restriction) and increased parenchymal and leptomeningeal contrast enhancement in a holo-hemispheric distribution with frequent basal ganglia and cerebellar involvement [ 14 , 39 ].…”
Section: Posterior Reversible Encephalopathy Syndrome (Pres) In Covidmentioning
confidence: 99%
“…Along with the common use of immunomodulatory medications, these associated characteristics make this pandemic disease a perfect storm for the development of PRES. [ 43 , 44 ] A larger study of 278 patients with confirmed COVID-19 undergoing imaging demonstrated a 1.1% prevalence of PRES. MRI as an imaging modality had a higher yield in detecting cases, demonstrating a 3.9% prevalence of PRES.…”
Section: Introductionmentioning
confidence: 99%